Does autogenous bone graft work? A logistic regression analysis of data from 159 papers in the foot and ankle literature. Issue 3 (September 2015) - Lareau, Craig R.; Deren, Matthew E.; Fantry, Amanda; Donahue, Rafe M.J.; DiGiovanni, Christopher W.
Highlights We examine all available arthrodesis literature of the foot and ankle. Hypothesized that autogenous bone graft is superior to allograft or no graft. A significant lack of standardization and consistency exists across this data. No statistically significant association between bone graft type and other variables. Autograft and cancellous allograft favored, but not statistically significant.